Analisis Kebutuhan LKS Berbasis STEM Kelas XI Materi Fluida Dinamis - Nurul Komariyah; Hadma Yuliani; Nur Inayah Syar (Kappa Journal, 2021)
This research was conducted to complete the teaching materials, namely the worksheets used by teachers. This research is also based on the lack of use of student worksheets in SMA Negeri 5 Palangka Raya. Teachers often use textbooks and modules in the learning process rather than using student worksheets. The purpose of this study was to determine the needs of students for the use of STEM-based student worksheets in class XI on dynamic fluid material. The research instrument used was a questionnaire distributed to students via google form. Based on the results of the needs analysis, 74.1% of students stated that physics is difficult to learn and understand, because it uses a lot of formulas. The online system is the main reason students have difficulty understanding physics material. Teaching materials that are often used by teachers in learning physics are textbooks. Student modules and worksheets are used very rarely and have a fairly low percentage of 33.3% and 25.9%, respectively. Therefore, it is necessary to develop STEM-based worksheets on dynamic fluid materials.